An agreeable answer to a pro-theism/anti-theism question - Mawson, T (Routledge, 2017)
In this chapter, I address some difficulties that stand in the way of reaching an answer that will be agreeable across the Theist/Atheist divide to a particular Pro-theism/Anti-theism question, the question I call ‘the’ comparative Pro-theism/Anti-theism question. Really, one might say, ‘the’ comparative Pro-theism/Anti-theism question is two questions, one for the theist and one for the atheist. For the theist: would God’s not existing have been better or worse than is His existing? For the atheist: would God’s existing have been better or worse than is His not existing? Assuming that theist and atheist alike should agree that the issue of whether or not there’s a God concerns a metaphysical necessity and thus that each should think of themselves as involved in counter-possible reasoning when addressing their variant of ‘the’ comparative Pro-theism/Anti-theism question, I shall argue that the difficulties they face in reaching an agreement on its answer, whilst not insignificant, can be overcome, at least to an extent. I shall tentatively suggest that an answer that I shall call ‘Weak Pro-Theism’ emerges as one that is agreeable across the Theist/Atheist divide, agreeable as what I shall call the ‘lower epistemic bound’ to ‘the’ correct answer to ‘the’ comparative question. More specifically, the theist should answer his variant of the question by saying that it would have been somewhat worse (or at least no better) were God not to have existed. The atheist should answer his variant by saying that it would have been somewhat better (or at least no worse) were God to have existed. I shall argue that arguments for a stronger Pro-theistic conclusion to this question largely wait on a resolution to the Theism/Atheism question.